Cross-sectional observational study of nipple and areola changes during pubertal development and after menarche in 313 Italian girls - De Sanctis, Vincenzo; Elhakim, Ihab Zaki; Soliman, Ashraf T; Elsedfy, Heba; Soliman, Nada; Elalaily, Rania (Acta Biomedica Atenei Parmensis, 2016)
Obiective: To describe the characteristics of nipple development during puberty in Italian females. In addition this is compared with Tanner criteria for breast and pubic hair development at different stages and correlated with body mass index (BMI) and the menstrual age. Design: Cross-sectional observational study. Setting: Italian children and adolescents consecutively assessed at the Endocrine and Adolescent Outpatient Clinic of Private Accredited Quisisana Hospital of Ferrara. Partecipants: Healthy females 2-20 years, belonging to Italian middle socio-economic class. Study duration: This study was conducted for a total period of 39 months from September 2012 to December 2015. Methods: Demographic characteristics, age at menarche and menstrual duration, anthropometry (weight, height, BMI) and pubertal status (breast and pubic hair) were evaluated. The greatest diameters of the erect nipple and areola sizes were measured in all subjects in supine position using a plastic template with graduated circular cut-outs or a transparent graduated ruler. Results: Significant increments in nipple diameter were noted between Tanner’s stages B1, B2, B3, B4 and B5 but the differences between stages B1 vs B2, B3 vs B4, B4 were more significant (p